‘God made a farmer’: stewardship cosmovisions of the good farmer - Baumer, Samuel (My University, 2025)
In the Anthropocene, the Earth, farmers, rural communities, and eaters are suffering from the dominant, industrial form of agriculture. Because of the diverse impacts of agriculture for people and ecosystems, many have sought to better understand farmer motivations and behaviors. In the U.S. Midwest, “stewardship” has been shown to be a foundational principle of farmers’ moral identities as “good farmers.” However, much research tends to reflect more of an etic rather than emic understanding of stewardship, limiting our understanding of key questions about how and why farmers adopt or change perspectives and practices. Because stewardship has been shown to imply or assume a divine responsibility to care for something unowned, exploring farmer “cosmovisions” –their interconnected spiritual, natural, and social worlds–can better illuminate the heterogeneity within and between groups that may not conform normative scripts of religiosity, spirituality, or life philosophy. This project takes a process-relational approach to ethnographic interviewing to explore stewardship as a foundational principle, or value, among farmers across a diversity of farms and cosmovisions in the Great Plains of the Midwest U.S. This research identifies varied meanings of “stewardship” among three relatively distinct assemblages of principles and practices.
Keywords: Stewardship; Good farmer; Cosmovision